HOW DOES THE STATE COMBAT FALSE AND COUNTERFEIT MEDICINES - Yokubova U. M. (Scholar Express Journals, 2024)
The purpose of the study is to analyze and evaluate the effectiveness of measures taken by the state to combat false and counterfeit medicines. The study aims to identify key strategies and tools used to prevent the production and distribution of counterfeit medicines, and to assess their impact on the quality and safety of medicines available to the public.
Keywords: Falsification; medicines; quality control; liability